Sea Turtles for Ocean Research and Monitoring: Overview and Initial Results of the STORM Project in the Southwest Indian Ocean - Bousquet, Olivier; Dalleau, Mayeul; Bocquet, Marion; Gaspar, Philippe; Bielli, Soline; Ciccione, Stéphane; Remy, Elisabeth; Vidard, Arthur (Frontiers in Marine Science, 2020)
Surface and sub-surface ocean temperature observations collected by sea turtles (ST) during the first phase (Jan-2019 – April 2020) of the Sea Turtle for Ocean Research and Monitoring (STORM) program are compared against in-situ and satellite temperature measurements, and later relied upon to assess the performance of Glo12 ocean model forecasts over the west tropical Indian Ocean. The evaluation of ocean temperature profiles collected by STs against collocated ARGO drifter measurements show good agreement, with imperceptible discrepancies at all sample depths (0-250m). Comparisons against various operational satellite sea surface temperature (SST) products indicate a slight overestimation of ST-borne temperature observations of ~ 0.1° +/- 0.6° that is consistent with expected uncertainties on satellite derived SST data. Comparisons of ST-borne surface and subsurface temperature observations against Glo12 operational ocean model forecasts demonstrate the good performance of modelled surface and subsurface (<50m) temperature predictions in the West tropical Indian Ocean, with mean bias (resp. RMS) in the range of 0.2° (resp. 0.5 - 1.5°). At deeper depths (>50m), the model is however shown to significantly underestimate ocean temperatures as already noticed from global evaluation scores performed operationally at the basin scale. The distribution of model errors also shows significant spatial and temporal variability in the first 50 m of the ocean, which will be further investigated in the next phases of the STORM project.